Visitors' View on the Dialect of Cheboksary - 2 - Tamara N. Erina; Eduard V. Fomin (Publishing house "Sreda", 2021)
The research continues the cycle of the group of authors devoted to the problem of regional variation of the Russian literary language. The paper analyzes the observations of newcomers over the speech of Cheboksary residents. This technique is new in the linguocheboksaryka and, in theory, should help in replenishing the markers of the Cheboksary region with elements that are familiar to the permanent residents of the city, but from the point of view of the Russian literary language are specific uses. As a result of the study, the authors come to the following conclusions: from the point of view of orthology, the speech of Cheboksary residents is distinguished by stable peculiar features, which, however, are already recognized by the inhabitants of the city as such; in the aspect of research methods, the method of talking with visitors can work fully at the beginning of research, at an advanced stage of developing the problem, its effectiveness decreases, but this conclusion does not become a condition for abandoning the method, but requires an increase in the number of respondents and complication of the conversation. The work also presents excerpts from conversations that made Cheboksary residents think about the quality parameters of their speech and the speech of townspeople in general. The study seems to be important for understanding the Cheboksary regioelct of the region as a phenomenon of the Russian language.